Influence of government ethnic policies on national unity in Iran (1997-2005) - Khorshidi, Majid (2013)
Iran is a multi-ethnic nation-state. All Iranian ethnic groups are indigenous and well integrated in general, but conflict and disagreement may occur when the issues of religion and language are being manipulated in politics. Therefore, preserving and promoting of national unity have been the most significant issue for all Iranian governments especially during the recent one hundred years. Khatami’s administration (1997-2005) as a reformist government applied its own policies to cope with the diversity. Undoubtedly, the policies had their consequences, and influenced on national unity among ethnic groups. While the rivals of the administration argue the harmful effects of these policies on national unity through increasing ethnic demands, its advocates praise the applied policies due to their influences on promoting national unity. Based on the above problem, the purpose of this study is to describe the political and cultural demands of ethnic groups in Iran during Khatami’s administration, the administration’s responses to the demands, and the influences of the administration’s policies on level of national unity among the ethnic groups. Based on the “systems theory” which indicates impacts of the demands and the systems responses to these demands, this research has explored the ethnic groups’ demands and the administration’s policies responding to these demands and finally,the influences of these policies on the national unity among ethnic groups. The research followed qualitative approach and the primary data were collected through semi-structured interviews. The selection of respondents was based on purposive sampling method. The respondents were 23 persons from three categories of the informants: ethnic, administrative, and academic elites. Moreover, to enrich the data collected through the interviews, documentary data were used in some parts. For analysing of the data, the study applied qualitative content analysis. The results indicate that Iranian ethnic groups due to their long co-existence and native nature have no secessionist demands but they have their own demands specially participation in power, reduction in discrimination, and cultural rights. The presidency election in 1997, which led to Khatami’s winning, created a new atmosphere for the ethnic groups to express their demands. Khatami and his administration regarding his reformist ideas met the demands with positive attitudes, and chose a smart way to respond the ethnic groups’ demands without provoking the concerns of the majority of the Iranian society. Most of the administrations’ policies were run by the name of citizens’ rights and empowering the civil society. Under this approach, the administration responded many the ethnic demands. For the first time in the history of Iran, the administration executed the election of city councils, which played a remarkable rule in the ethnic groups’ participation. In addition, some policies were followed in case of removal of discrimination and repression. The cultural demands were also responded. The collected data shows, to some extent, it was a success in achieving the aims of the policies, however due to the duality of the political system in Iran and the competition between the reformists and conservatives, the policies met with some obstacles and limitations.